Anti-androgen monotherapy versus gonadotropin-releasing hormone agonists in men with advanced, non-metastatic prostate cancer: a register-based, observational study. (2nd January 2019) - Thomsen, Frederik Birkebæk; Bosco, Cecilia; Garmo, Hans; Adolfsson, Jan; Hammar, Niklas; Stattin, Pär; Van Hemelrijck, Mieke
Abstract: Background: In randomised controlled trials, men with advanced, non-metastatic prostate cancer (PCa) treated with anti-androgen monotherapy (AA) had similar all-cause mortality as men treated with gonadotropin-releasing hormone (GnRH) agonists. Using real-world evidence (i.e., observational data), we aimed to further assess the difference in mortality between these two drug categories. Material and Methods: We emulated a trial using data from Prostate Cancer data Base Sweden 3.0. We specifically focused on men diagnosed in 2006–2012 with high-risk PCa who had no distant metastasis. They either received primary hormonal therapy with AA ( n = 2078) or GnRH agonists ( n = 4878) who were followed for a median time of 5 years. Risk of death from PCa and other causes was assessed using competing risk analyses and Cox proportional hazards regression analyses, including propensity score matching. Results: The cumulative 5-year PCa mortality was lower for men treated with AA (16% [95% confidence interval, CI, 15–18%]) than men treated with GnRH agonists (22% [95% CI 21–24%]). The 5-year other cause mortality was also lower for men on AA (17% [95% CI 15–19%] compared to men on GnRH agonists (27% [95% CI 25–28%]). In regression analyses, the risk of PCa death was similar, GnRH agonists versus AA (reference), hazard ratio (HR) 1.08 (95% CI 0.95–1.23), but the risk of death from all causes was higher for men on GnRH agonists, HR 1.23 (95% CI 1.13–1.34). Consistent results were seen in the propensity score-matched cohort. Conclusion: Our results indicate that the use of AA as primary hormonal therapy in men with high-risk non-metastatic PCa does not increase PCa-specific mortality compared to GnRH. Using AA instead of GnRH agonists may result in shorter time on/exposure to GnRH-treatment, which may reduce the risk of adverse events associated with this treatment.